Role of transvaginal ultrasound in predicting preterm labor in singleton pregnancies - Beigh, Mehbooba; Mir, Mohammed Farooq; Amin, Rifat; Shafi, Simrath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preterm delivery (PTD) is a major cause of perinatal morbidity and mortality. Objective of present study was to identify the women at risk of preterm delivery with the help of trans-vaginal ultrasound by assessing cervical length changes, funneling of lower uterine segment, cervical dilatation. Methods: A prospective study was carried out over a period of 2 years on 50 patients with 24-36 weeks of gestation who clinically presented with signs of threatened preterm labor and were subjected to transvaginal sonographic measurement of cervical length. Results: Prediction of spontaneous preterm birth at <37 weeks of gestation with cervical length to be 2.75 cm has sensitivity of 95%, specificity of 96.5%, positive predictive value of 86.36% and negative predictive value of 98.7%. Conclusions: Transvaginal ultrasonography is the reliable, reproducible and objective method to assess cervix and to predict the risk of preterm delivery.